ANALYSIS OF THE EFFECT OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON STOCK PRICES IN MANUFACTURING COMPANIES IN THE GARMENT AND TEXTILE SUB-SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018-2023 (International Journal of Innovative Technologies in Economy, 2025)
This research investigates the impact of Current Ratio and Debt to Equity Ratio on Stock Price. This study is classified as associative study. The population in this study is the Garment and Textile Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2023, totaling 24 companies. This study examined 6 companies and collected 36 observation data points through purposive sampling. Analysis was conducted using secondary data, incorporating various statistical tests such as descriptive statistics, tests for classic assumptions, t-tests, F-tests, and determination coefficients. Initial results indicate that the Stock Price is not significantly influenced by the Current Ratio, whereas the Debt To Equity Ratio has a considerable impact on Stock Price. Additionally, it is discovered that both the Current Ratio and Debt to Equity Ratio contribute to determining Stock Price.